Hubungan Tingkat Pengetahuan HIV/AIDS dengan Perilaku Seks Bebas Pada Siswa Kelas XII di SMAN X Sleman - Kresensia Lestari Tende; Riadini Wahyu Utami; Mahindria Vici Virahaju (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2026)
The problem of HIV and AIDS represents a significant health, economic, social, and psychological challenge worldwide, including in Indonesia. HIV (Human Immunodeficiency Virus) is a virus that weakens the immune system, while AIDS (Acquired Immuno-Deficiency Syndrome) is a condition of immune system deficiency caused by HIV infection. Based on the DIY Provincial Health Profile, 916 new HIV cases were detected in 2022, with the highest prevalence recorded in Sleman Regency (340 cases) and the lowest in Kulon Progo Regency (28 cases). The total cumulative cases reached 6,784, with a male dominance of 69.1%. Preliminary interviews conducted with students at SMAN X Sleman revealed a lack of awareness regarding the signs, symptoms, transmission, and impacts of risky sexual behavior. Consequently, this study aimed to determine the relationship between HIV/AIDS knowledge levels and risky sexual behavior among Grade XII students at SMAN X Sleman. This analytical research employed a correlational study with a cross-sectional design. The research sample consisted of 58 Grade XII students selected through simple random sampling. Data were analyzed using the Chi-Square test. The results showed that there was no significant relationship between the level of HIV/AIDS knowledge and risky sexual behavior, with a p-value of 0.627 (p > 0.05).